Collecting Hair Samples in Online Panel Surveys: Participation Rates, Selective Participation, and Effects on Attrition - Mario Lawes; Clemens Hetschko; Joseph W. Sakshaug; Michael Eid (Survey Research Methods)
Combining survey data with biological information allows examining complex interrelationships between a person’s physiological status and behavioral or health-related outcomes. Given the increasing importance of online surveys and smartphone-based research, a crucial question is whether biomarker collection can be embedded in online surveys without any face-to-face interaction. The present study addresses this question and investigated participation rates and selective participation in a longitudinal hair collection study that was embedded within an app-based smartphone panel survey on the well-being of German jobseekers. The study further examined the association between participating in the first hair collection wave and panel attrition. The results indicate that the vast majority (81%) of individuals was willing to participate in the first hair collection wave with only a few selection effects. Only older age and higher levels of perceived stress were modestly associated with the stated willingness to participate in the first hair collection wave. The strongest selectivity was induced by the inevitable exclusion of individuals with short hair styles, which led to an underrepresentation of men. Furthermore, respondents’ purported willingness to participate in the first hair collection wave and their actual participation was largely disconnected. This lack of compliance decreased in subsequent collection waves. Notably, participating in the first hair collection wave was positively related to long-term panel participation. Overall, the study underlines the general feasibility of integrating biomarker collections into online surveys.